High serum total cholesterol is associated with suicide mortality in Japanese women. (26th May 2017) - Svensson, T.; Inoue, M.; Sawada, N.; Charvat, H.; Mimura, M.; Tsugane, S.; ,
Abstract : Objective: To investigate the association between serum total cholesterol (TC) and suicide using a large general population cohort with long follow‐up times. Method: Analyses included 16 341 men and 28 905 women aged 40–69 from the Japan Public Health Center‐based Prospective Study followed from 1990 to 2012. TC levels were defined per clinical guidelines: low (<4.66 mmol/l [180 mg/dl]), normal (4.66–5.70 mmol/l [180–220 mg/dl]), and high (≥5.70 mmol/l [220 mg/dl]). Cox proportional hazards regression models were used to determine hazard ratios (HR) and confidence intervals (CI) for suicide according to TC level. Mean follow‐up time was 19 years for men and 20 years for women. Results: There were 185 suicides (men: 107; women: 78) during follow‐up. Compared to women with normal TC, women with high TC had a significantly increased risk of suicide (HR = 1.90, 95% CI, 1.13–3.19). Incremental increases (0.26 mmol/l [10 mg/dl]) of low‐density lipoprotein (HR = 1.11, 95% CI, 1.02–1.21) and non‐high‐density lipoprotein cholesterol (HR = 1.09, 95% CI, 1.01–1.18) were also associated with increased risk of suicide in women. There was no association between TC levels, or lipid fractions, and suicide in men. Conclusion: High TC levels may be associated with an increased risk of suicide in women.